Fiber to the building network design for tokong nanas building with multi applications - Farhan Ghifari Adhitya; Athallah Favianauvally Nadhasya; Fahrul Halim Jaka Kahayan; Uke Kurniawan Usman; Akhmad Hambali (Universitas Telkom, 2026)
This research aims to implement a Fiber to the Building (FTTB) system using Next Generation Passive Optical Network (NGPON) technology at Tokong Nanas Building, Telkom University. The design focuses on enhancing connectivity and data capacity to meet lecture needs, considering environmental and business aspects, and internet penetration potential in Indonesia. The network implementation starts from the Cijawura Automated Telephone Center (STO) to Tokong Nanas Building using two resilient lines: the Kordon Market line to Optical Distribution Cabinets (ODC) coded as FED, and the Cikoneng line to ODCs coded as FBL. The network extends to the Mini Optical Line Termination (OLT) at the Information Technology Center (PuTI), from the Mini OLT the feeder cables direct to the internal ODC to be flowed into Tokong Nanas Building. The design is create using location and building mapping software and achieves QoS values meeting eligibility standards: Bit Error Rate (BER) ≤ 10-9, Signal to Noise Ratio (SNR) ≥ 21.5 dB, Q-Factor ≥ 6, and Link Power Budget (LPB) below -28 dBm. The Bill of Quantity (BoQ) estimates the design cost through Kordon Market and Cikoneng at Rp7,199,387,990.30, with a total revenue over 10 years of Rp66,948,188,836.00.